“Masones salvadoreños e instrucción intelectual femenina: El Salvador, 1875-1887” - Vázquez Monzón, Olga Carolina (2013)
This paper analyses the political influence of Freemasons such as Baltasar Estupinian, Rafael Reyes, Rafael Zaldívar, Antonio J. Castro, Manuel Delgado and Rafael Meza who promoted instruction for women in El Salvador, at the end of the 19th century. Through the review of printed papers of the time, in this study we have collected speeches of opinion, decrees, regulations and news that link these freemasons with activities that promote women ́s education, creating educational institutions for women, the extended plan studies, providing scholarships or fee waivers for those who wanted to continue their secondary education and higher education.